International Expansion of Indian Pharmaceutical Companies: Trends, Strategies, and Outlook - Singh Deeksha,; Jadhav Diksha, (Asian Journal of Pharmaceutical Research and Development, 2025)
The Indian pharmaceutical industry has rapidly grown from being a domestic generics supplier to a global healthcare contributor. Today, Indian companies supply nearly 20% of the world’s generic medicines and around 60% of vaccines, positioning the sector as a global lifeline. This paper reviews the industry’s expansion strategies, export trends, and future opportunities while highlighting regulatory hurdles, raw material dependencies, and the industry’s future lies in biosimilars, specialty medicines, and innovation-led growth.